Penerapan Pendidikan Milestones Character di SMK Nasional Mojosari - Syafitri Wenda Pratama; Jasmine Noer Aini; Mulia Putri Khasanah; Friskha Nur Hida Rotus Sya’roni; Aditya Nata Widigda; Wawan Hermawan; Asih Andriyati Mardliyah; Susiawati Susiawati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Education is an essential need that must be fulfilled throughout life and plays an important role in building the nation's character. In Indonesia, character education is currently a concern of the community, and is a social problem that has not been resolved. This study aims to describe the application of character education at SMK Nasional Mojosari. The methods used include quantitative descriptive, qualitative, and observational. The research population consisted of students in grades 10 and 11 from five majors, with data collection techniques through unstructured interviews, questionnaires, and non-participant observations. The research instrument is tested for the validity of its construction to ensure the reliability of the data. The results of the study show that the implementation of character education—including discipline, responsibility, honesty, care, and cooperation—is going well, supported by the curriculum implemented and the positive views of school principals and teachers on the importance of instilling character values in students.